INDIKASI TERJADINYA PELANGGARAN HAK ASASI MANUSIA OLEH DENSUS 88 ANTI TEROR DALAM PENANGANAN TERDUGA TERORIS - Pujantini Pujantini; Fakhlur Fakhlur (Qiyas : Jurnal Hukum Islam dan Peradilan, 2022)
Abstract : In carrying out its duties, Densus 88 AT needs to be supervised by an independent institution that oversees the work of the anti-terror unit of Densus 88 because so far there are indications that there is no supervision or evaluation of the performance of Densus 88, so there is an impression of being out of control.Komnas HAM did not want to comment on the pros and cons of the disbandment of Densus 88 AT, because the agency agreed that terrorists should be dealt with, but arbitrary actions should not be taken. According to Komnas HAM, shooting dead against suspected terrorists should be avoided unless it is absolutely necessary and must be proven transparently and legally accountable.Keywords: Human Rights Violation, Densus 88 Anti-Terror, Suspected Terrorist